2020
DOI: 10.1101/2020.05.21.109520
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

How cells determine the number of polarity sites

Abstract: The diversity of cell morphologies arises, in part, through regulation of cell polarity by Rho-family GTPases. A poorly understood but fundamental question concerns the regulatory mechanisms by which different cells can generate different numbers of polarity sites. Theoretical models of polarity circuits develop multiple initial polarity sites, but then those sites engage in competition, leaving a single winner. The timescale of competition slows dramatically as GTPase concentrations at polarity sites approach… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(26 citation statements)
references
References 59 publications
(101 reference statements)
4
22
0
Order By: Relevance
“…While in model (1) the type of pattern depends only on the total conserved quantity of the patterning protein, in the real GTPase systems, this will also be controlled by the ratio of the quantities of GTPase and its positive-feedback GEF. In the analysis of the behavior of the multivariable model for the Cdc42 cluster formation, it has been observed that the component present in the least amount defines the competition behavior of the pattern [40]. This fully confirms the early results of [18] that, following the contemporary experimental data, assumed that Cdc42 is in large molar excess over its positive-feedback activator GEF Cdc24 (~300:1).…”
Section: Implications For Cellular Morphogenesissupporting
confidence: 74%
See 3 more Smart Citations
“…While in model (1) the type of pattern depends only on the total conserved quantity of the patterning protein, in the real GTPase systems, this will also be controlled by the ratio of the quantities of GTPase and its positive-feedback GEF. In the analysis of the behavior of the multivariable model for the Cdc42 cluster formation, it has been observed that the component present in the least amount defines the competition behavior of the pattern [40]. This fully confirms the early results of [18] that, following the contemporary experimental data, assumed that Cdc42 is in large molar excess over its positive-feedback activator GEF Cdc24 (~300:1).…”
Section: Implications For Cellular Morphogenesissupporting
confidence: 74%
“…However, two different types of genetic perturbation aimed at weakening the spot competition produced the desired result-the simultaneous formation of two or more buds. Since these pioneering analyses, our understanding of competition between the yeast Cdc42 clusters has been substantially advanced both experimentally and theoretically, nevertheless, the problem continues to attract the interest of researchers [19,[40][41][42][43].…”
Section: Yeast Bud and The Emergence Of The Competition Concept In Thmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the present study was conducted with the hypocotyl hook of model plant Arabidopsis , we speculate that such a “bending‐triggered curvature” model may also be applied to the apical arc/hook development of other plant species, in which the arc/hook structures are diversely derived from apices of epicotyls, true leaf petioles, cotyledon petioles, inflorescent stems, and so on (Darwin and Darwin, 1896). Furthermore, the two‐stage “trigger‐then‐amplify” growth behaviors are seen not only at the multicellular level, such as the touch‐triggered coiling of leaf tendrils or stem tendrils in climbing plants (Jaffe and Galston, 1968; Braam, 2005), but also at the single cellular level, such as bud‐site selection in budding yeast and germination site selection in Arabidopsis pollens (Liu et al, 2018; Chiou et al, 2021). How relevant those similar growth behaviors may exhibit at the molecular level should be an interesting direction for future investigations.…”
Section: Discussionmentioning
confidence: 99%